FRI0167 LONG TERM CLINICAL OUTCOME IN SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS FOLLOWED FOR MORE THAN 20 YEARS IN THREE ITALIAN TERTIARY REFERRAL CENTERS: THE MILAN SYSTEMIC LUPUS ERYTHEMATOSUS CONSORTIUM (SMILE) COHORT. (2nd June 2020) - Gerosa, M.; Ramirez, G. A.; Bellocchi, C.; Argolini, L. M.; Moroni, L.; Cornalba, M.; Farina, N.; Dagna, L.; Caporali, R.; Bozzolo, E.; Beretta, L.
Abstract : Background: the prognosis of Systemic lupus Erythematosus (SLE) patients has significantly improved over time, raising the need for more data about disease activity and damage accrual in the long term. Objectives: to investigate the risk of long term disease activity and to identify viable prognostic markers for disease flares in SLE patients with long standing disease Methods: data on SLE patients regularly followed at ASST PINI-CTO, Fondazione Ca' Granda Policlinico and Ospedale San Raffaele, Milan (Milan Systemic Lupus Erythematosus Consortium, SMiLE, cohort) with disease duration ≥ 20 years, were retrospectively analyzed. Organ involvement as per the British Isles Lupus Assessment Group (BILAG) definitions was recorded along with achievement of clinical and complete remission (CR and CCR: clinical SLEDAI =0, PGA <0.5 and no prednisone or immunosuppression ± negative serology) and lupus low disease activity state (LLDAS) at 15 (T15) and 20 (T20) years of follow up. Damage accrual was estimated according to the SLE International Collaborating Clinics/American College of Rheumatology damage index (SDI). Results: data from 168 patients (table 1 ) were available for analysis. Remission (CR+CCR) and LLDAS were achieved in 22% and 61% at T15 and 25% and 71% at T20. LLDAS was not associated with a history of involvement in any BILAG domain, but it was inversely associated with treatment with mycophenolate at any time (50 vs 23% treated vs not treated; p=0.02). SDI>0 was found in 49% patients at T15 and in 71% at T20. LLDAS at T15 was associated with lower flare rates in the following five years (HR= 0.395, 95%, CI=0.239-0.653; Figure, left panel; p<0.001). The risk of flaring for LLDAS was largely comparable to CCR and CR (Figure, middle panel). In the T15-T20 timeframe, 37% of patients had a flare. Patients with both low complement and anti-dsDNA positivity at T15 had an increased risk of flaring compared to serologically inactive patients (HR=2.86, 95%, CI=1.572-5.19; Figure right panel). Flaring patients were more likely to show an increase in SDI from T15 to T20 (37% vs 9% in patients with stable SDI; p<0.001) Conclusion: LLDAS is common in SLE patients with long disease duration although up to 37% of patients with 15-year disease duration may experience a flare during the following 5 years. The flare risk increases with failure to attain LLDAS at T15 and with active serology. Late flares associate with damage accrual. References: [1]Aringer M, Ann Rheum Dis. 2019; Franklin K, Ann Rheum Dis 2019 Disclosure of Interests: Maria Gerosa: None declared, Giuseppe Alvise Ramirez: None declared, Chiara Bellocchi: None declared, Lorenza Maria Argolini: None declared, Luca Moroni: None declared, Martina Cornalba: None declared, Nicola Farina: None declared, Lorenzo Dagna Grant/research support from: Abbvie, BMS, Celgene, Janssen, MSD, Mundipharma Pharmaceuticals, Novartis, Pfizer, Roche, SG, SOBI, Consultant of: Abbvie, Amgen, Biogen, BMS, Celltrion, Novartis, Pfizer, Roche, SG, and SOBI, Roberto Caporali Consultant of: AbbVie; Gilead Sciences, Inc.; Lilly; Merck Sharp & Dohme; Celgene; Bristol-Myers Squibb; Pfizer; UCB, Speakers bureau: Abbvie; Bristol-Myers Squibb; Celgene; Lilly; Gilead Sciences, Inc; MSD; Pfizer; Roche; UCB, Enrica Bozzolo: None declared, Lorenzo Beretta Grant/research support from: Pfizer